Characterizing ProstivaTM RF Treatments of the Prostate for BPH with Gadolinium-Enhanced MRI - Christian Huidobro; Benjamin Larson; Samuel Mynderse; James J. Myers; David Busel; Cristian Acevedo; Thayne R. Larson; Lance A. Mynderse (The Scientific World Journal)
Transurethral needle ablation (TUNA) is an accepted and effective therapy for the treatment of lower urinary tract symptoms (LUTS) due to benign prostatic hyperplasia (BPH). ProstivaTM (Medtronic, Shoreview, MN) is the newest-generation device, which includes a new needle design and radio frequency (RF) generator. This device creates temperatures of 120°C and necrotic lesions in less than 2.5 min. Using previously described techniques, we analyzed dynamic, gadolinium-enhanced MRIs to characterize the ablative properties of the new ProstivaTM RF device.